Sucked in by eDNA – a promising tool for complementing riverine assessment of freshwater fish communities in Aotearoa New Zealand. Issue 3 (2nd October 2021) - David, Bruno O.; Fake, Daniel R.; Hicks, Andy S.; Wilkinson, Shaun P.; Bunce, Michael; Smith, Josh S.; West, David W.; Collins, Katie E.; Gleeson, Dianne M.
ABSTRACT: There is increasing interest in the health of waterways in Aotearoa New Zealand. The National Policy Statement for Freshwater Management 2020 (NPS-FM) places a greater onus on resource managers to report on the state of freshwater ecosystem health, including fish. Routine fish monitoring is time intensive and is principally conducted in 'wadeable' stream reaches. In comparison, environmental DNA (eDNA) sampling is a relatively recent and rapid technique that likely detects fish and other vertebrate and invertebrate taxa over a broader spatial scale. In this study, we present data for five wadeable streams comparing diversity derived from multi-year standardised electrofishing with eDNA samples collected from the same reaches. Further, we explore whether the number of eDNA monitoring 'reads' for species at a site may provide an approximate (semi-quantitative) indication of their 'near field' relative abundance based on one-pass electrofishing captures. Results indicated that while some aspects of the methodology require fine-tuning, eDNA sampling shows substantial promise for complimenting state of the environment (SOE) reporting for describing fish diversity in wadeable streams. The use of aquatic eDNA monitoring to provide a cost-effective indication of broader catchment scale biodiversity (e.g. birds and exotic pests) in wadeable and non-wadeable streams is also discussed.